Implementation Implementasi Undang-Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi (PDP) Pada Dinas Komunikasi Dan Informasi Di Kabupaten Majalengka - Andi Masrich; Tri Yanto; Edy Supriyono (Post Graduate School of Government Science, 2026)
This study discusses the Implementation of Law No. 27 of 2022 concerning Personal Data Protection at the Communication and Informatics Service in Majalengka Regency. The phenomenon that occurs with digitalization is very vulnerable regarding personal data protection because it is vulnerable to leaks, misuse, and cyber attacks . The main objective of this study is to analyze, identify obstacles or challenges and formulate strategies for the Implementation of Law No. 27 of 2022. The research method used is a descriptive research method with a qualitative approach. The results of this study indicate that the implementation of the Personal Data Protection Law at the Majalengka Regency Communications and Information Office is still in the regulatory and infrastructure strengthening stage. Despite the existence of supporting regional policies, implementation still faces challenges in terms of regulatory understanding, human resources (HR), and information technology readiness to securely manage personal data. Government employees' awareness and understanding of personal data protection still needs to be improved. Interviews and observations indicate that many employees still do not fully understand their rights and obligations regarding personal data management, which can increase the risk of data breaches or leaks. However, implementation has shown significant progress in increasing the efficiency and transparency of public services. However, challenges in infrastructure, human resources, and data security still need to be seriously addressed. Further efforts are needed to strengthen service integration and improve public digital literacy to optimally achieve these goals.